THE INFLUENCE OF BUDGET PARTICIPATION AND INFORMATION SHARE ON BUDGET QUALITY & SLACK: A CASE OF IRAQI PUBLIC UNIVERSITIES BUDGETARY PROCESS - Aziz, Aziz Mohammed (PT. Antis International Publisher, 2026)
Objective: Iraqi Public universities confront a wide range of difficulties as a result of the complex interactions between budgetary quality and slack in the higher education sector, and in the context of public higher education institutions this article explores the complex issues related to budget participation, budget quality, budgetary slack, government expenditure transparency, and information sharing. Method: The analytical method used in this research is structural equation modeling (SEM) to determine the causal relationship between latent variables contained in structural equations, with the analysis tool Smart PLS, using quantitative methods through data collection by distributing questionnaires to teachers, of which 150 were returned and 148 were usable. Result: Based on the results of data analysis, it is concluded that there is a significant relationship between budget participation, information sharing and budget quality, and in addition there is a significant relationship between budget quality and budgetary slack, while government budget transparency does not show a clear link with budget quality in service rotation; furthermore, problems arise in universities when faculty and staff are not actively engaged in budgeting, as hierarchical structures tend to disregard faculty needs, resulting in wasted time and energy, even though budgeting itself reflects how institutions collaborate to make systems fit together. Novelty: Beyond these findings, the study provides recommendations and frontline insights for public higher education cohorts facing these issues daily, positioning Participatory Budgeting (PB) as a pathway toward more inclusive decision-making, fostering transparency in government spending, and strengthening community authority in managing resources for better outcomes in public interests.